This preview shows pages 1–2. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.View Full Document
Unformatted text preview: Fibonacci sequences Jonathan L.F. King University of Florida, Gainesville FL 32611-2082, USA firstname.lastname@example.org Webpage http://www.math.ufl.edu/ squash/ 26 April, 2009 (at 12:08 ) Prolegomenon. The famous Fibonacci sequence ~ f := ( f n ) n = is defined by f := 0, f 1 := 1 and f n +1 = f n + f n- 1 . 1 : Let P and G be the Positive and neGative roots of Fib( x ) := x 2- x- 1 note ==== [ x- P ][ x- G ] . So P + G = 1 and P G = 1 . Moreover, P 2 = P + 1 and G 2 = G + 1 . 2 : Let := 5 and b := 1 5 . Certainly ~ f is some linear combination [ n 7 P n ] + [ n 7 G n ]. Thus n Z : f n = b [ P n- G n ] , 3 : since this formula gives correct values for f and f 1 . 4 : Theorem. For each integer N : [ f N ] 2 + [ f N- 1 ] 2 = f 2 N- 1 . 4a : Proof. Always, LhS(4 a ) is non-negative. And RhS(4 a ) is non-negative, even when N Z- , since f Odd is always non-negative. So ISTProve that the squares of LhS(4 a ) and RhS(4 a ) are equal. To this end, define) are equal....
View Full Document